Self Esteem Dan Group Cohesiveness Sebagai Pemoderasi Pengaruh Partisipasi Anggaran Pada Budgetary Slack - Dwiprayuda, Anak Agung Ngurah Bagus; Wiratmaja, I Dewa (E-Jurnal Akuntansi; Vol 26 No 1 (2019)DO - 10.24843/EJA.2019.v26.i01.p16, 2019)
Behavior management in the process of preparing a company's budget can lead to the tendency of managers in creating bugetary slack. The purpose of this study to obtain empirical evidence of the ability of self esteem and group cohesiveness as a moderator of the influence of budgetary participation on budgetary slack. This research was conducted at 22 BPR in Denpasar City. The technique of determining the sample in this research is purposive sampling technique, with the number of respondents as much as 84. The analysis technique used in this research is Moderated regression analysis (MRA). The results of this study indicate that both self esteem and group cohesiveness are able to moderate the influence of budgetary participation in budgetary slack at BPR in Denpasar city. The higher self esteem and group cohesiveness will weaken the effect of budgetary participation on budgetary slack. Keywords: budget participation, self esteem, group